Novel Active Food Packaging Films Based on Gelatin-Sodium Alginate Containing Beetroot Peel Extract - Moufida Chaari; Khaoula Elhadef; Sarra Akermi; Boutheina Ben Akacha; Mariam Fourati; Ahlem Chakchouk Mtibaa; Monia Ennouri; Tanmay Sarkar; Mohammad Ali Shariati; Maksim Rebezov; Slim Abdelkafi; Lotfi Mellouli; et al. (MDPI AG, 2022)
Currently, the exploration of natural colorants from vegetal waste has gained particular attention. Furthermore, incorporation of these natural sources into biopolymers is an encouraging environmentally friendly approach to establishing active films with biological activities for food packaging. The present study developed bioactive antioxidant films based on gelatin-sodium alginate (NaAlg) incorporated with aqueous beetroot peel extract (BPE). Firstly, the effects of combining gelatin-NaAlg and BPE at 0.25, 0.5, and 1% on the mechanical, physical, antioxidant, and antibacterial properties of the films were analyzed. With increasing BPE, mechanico-physical properties and antioxidant and anti-foodborne pathogen capacities were enhanced. Likewise, when added to gelatin-NaAlg films, BPE remarkably increased the instrumental color properties. Moreover, during 14 days of storage at 4 °C, the impact of gelatin-NaAlg coating impregnated with BPE on microbial and chemical oxidation and on the sensory characteristics of beef meat samples was periodically assessed. Interestingly, by the end of the storage, BPE at 1% limited the microbial deterioration, enhanced the instrumental color, delayed chemical oxidation, and improved sensory traits. By practicing chemometrics tools (principal component analysis and heat maps), all data provided valuable information for categorizing all samples regarding microbiological and oxidative properties, sensory features, and instrumental color. Our findings revealed the ability of gelatin-NaAlg with BPE as an antioxidant to be employed as food packaging for meat preservation.